Broadening of the Concept of Obscenity in the Draft of Indonesian Penal Code - Rezky, Ali; Haris, Oheo Kaimuddin (Hasanuddin University, 2018)
The reform of the Indonesian Penal Code (KUHP) is necessary to accommodate the noble values of Indonesian society. Therefore, Indonesian criminal law should reflect the basic principles, cultural values that live within the inner niches of Indonesian society as a living law. The inclusion of several forms of obscene acts that exist within the extended Draft Penal Code is a manifestation of the philosophical, sociological and juridical framework of the Indonesian society. The extension of the concept of obscenity in the Draft of Indonesian Penal Code is in accordance with the philosophy of the Indonesian nation that gives religious values a fundamental place Consequently, the expansion of the concept of obscenity in the Draft of Indonesia Penal Code can answer some of the problems faced by Indonesian citizens.